(untitled) (Annals of Medical Research, 2023)
Aim: Acne vulgaris and psoriasis vulgaris have a negative psychosocial impacts on patients’ lives and cause external and internal stigma. This study aims to compare the levels of internalized stigma in acne vulgaris patients with those of psoriasis patients and evaluate the effect of sociodemographic and clinical features on internalized stigma. Material and Methods: This cross-sectional and observational study included consecutive adult patients diagnosed with acne vulgaris or psoriasis vulgaris in dermatology outpatient clinics. Sociodemographic and clinical characteristics were recorded. The internalized stigma scale (ISS) was applied to participants. Total ISS scores and five subscales of the ISS were analyzed. Results: A total of 154 patients, 114 with acne vulgaris and 40 with psoriasis vulgaris, were included in the study. The mean ISS score in acne vulgaris patients was 28.1±13.8, and the mean ISS score in psoriasis vulgaris patients was 32.0±13.7. There was no significant difference in total ISS scores between acne vulgaris and psoriasis vulgaris patients. The social withdrawal subscale score in psoriasis vulgaris patients was significantly higher, but stigma resistance subscale scores were significantly lower than in acne vulgaris patients (p=0.042 and p=0.047, consecutively). Psoriasis vulgaris patients with visible lesions had higher total mean ISS scores than those without (p=0.034). The duration of psoriasis was significantly correlated with total ISS scores (rho= 0.333, p=0.036). Conclusion: Patients with acne vulgaris and psoriasis vulgaris have similar total internalized stigma scores. Psoriasis vulgaris patients exclude themselves from society more than acne vulgaris patients, while acne vulgaris patients can overcome the stigma more than psoriasis patients. The visibility and duration of the dermatologic disorder may be important factors in experiencing internalized stigma.